Dū risālah az ʿIzz al-Dīn-i Zanjānī : ʿUmdat al-ḥisāb wa-Qisṭās al-muʿādala fī ʿilm al-jabr wal-muqābala - Zanjānī', ʿIzz al-Dīn (Miras Maktoob, ISBN: 9789004365452., 2019)
Not much is known about ʿIzz al-Dīn Zanjānī's (d. 660/1262) personal life other than that at different times in his career he was in Mosul, Baghdad, Bukhara and Tabriz, where Naṣīr al-Dīn Ṭūsi (d. 672/1274) wrote his Tadhkira fi ʼl-hayʾa at his request. To posterity Zanjānī is maybe best known for his work on Arabic morphology, the Mabāḍiʾ al-taṣrīf , also known as Taṣrīf al-Zanjānī and al-ʿIzzī , on which many commentaries and supercommentaries were written. Zanjānī has four more works on linguistics, besides one work on astronomy and six treatises on mathematics, two of which are published in facsimile here. The first of these is his ʿUmdat al-ḥisāb on arithmetic and the second the Qisṭās al-muʿādala on equations. Following Zanjānī's own statements at the beginning of these treatises they were written for practical reasons, people in general standing in need of a good text on arithmetic, while the text on equations was especially relevant for jurists.